Pérez, Leda M. (ed.) (2018). La economía del cuidado, mujeres y desarrollo: perspectivas desde el mundo y América Latina. Fondo Editorial. Universidad del Pacífico. - Meneses Benítez, Marilyn (2025)
The book “La economía del cuidado, mujeres y desarrollo” analyzes the historical subordination of women to reproductive work, exploring its connection to capitalism and patriarchal domination. It examines the economic and social implications of the separation between productive and reproductive work, presenting conceptual frameworks for understanding the casualization of care work. The text proposes policy solutions that promote co-responsibility between the state, the market, the family and civil society, emphasizing the need for gender policies and better data collection to guarantee care as a right. Finally, different models of care policies are analyzed, including the familist and the defamiliarizing.